2DEG properties of AlScN/GaN and AlYN/GaN HEMTs determined by terahertz optical Hall effect - Stanishev, V.; Streicher, I.; Papamichail, A.; Rindert, V.; Paskov, P. P.; Leone, S.; Darakchieva, V. (Frontiers in Electronic Materials, 2025)
We present a contactless determination of the two-dimensional electron gas (2DEG) properties in AlScN/GaN and AlYN/GaN high electron mobility transistor (HEMT) structures using the terahertz optical Hall effect (OHE) over a temperature range of 20 K–360 K. The structures are grown on sapphire or 4H-SiC substrates by metalorganic chemical vapor deposition (MOCVD) and feature ∼10-nm thick barrier layers with Sc and Y contents ranging from 4.6% to 17.3% and 3.3% to 8.2%, respectively. The temperature dependencies of the 2DEG density and mobility parameters are analyzed and discussed in a comparative manner. Additionally, conclusions are drawn regarding the predominant scattering mechanisms at both low and room temperatures. Furthermore, the 2DEG effective mass parameter m* in AlScN/GaN and AlYN/GaN is determined for the first time. At low temperatures m* is found to be in the range 0.20−0.27m0, close to the value of 0.23m0 for bulk GaN. As temperature increases above 100 K, m* gradually rises reaching 0.33−0.39m0 at room temperature, consistent with findings for AlGaN/GaN HEMTs. The underlying causes of this temperature-dependent increase in effective mass are discussed, with a possible explanation linked to polaron effects and deviations from the classical Drude model.